Pengaruh Persepsi Harga dan Electronic Word of Mouth Terhadap Keputusan Pembelian di Maison Journal Coffee and Eatery Bukittinggi - Faiza, Ayu Nurul; Wulandari, Dwi Pratiwi (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2025)
This study aims to examine the influence of price perception and electronic word of mouth on consumers’ purchasing decisions at Maison Journal Coffee and Eatery in Bukittinggi. This research is motivated by the increasing number of coffee shops in Bukittinggi which urges business owners to understand the key factors that drive consumer interest and purchasing behavior. Price perception in this study is measured through indicators such as price affordability, alignment with product quality and benefits, and price competitiveness. Meanwhile, eWOM is assessed through positive reviews, product recommendations, frequency of reading reviews, and consumer confidence in making purchases based on online feedback. A quantitative approach with an associative method was used in this research. Data were collected through questionnaires distributed to 120 respondents who had previously made purchases at Maison Journal Coffee and Eatery Bukittinggi. The analysis technique employed was Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that both price perception and eWOM have a positive and significant effect on purchasing decisions, both partially and simultaneously. These findings highlight the importance of implementing pricing strategies that align with consumer perceptions and managing eWOM effectively by improving service quality and monitoring online reviews. This research contributes to the field of service marketing management, particularly in the culinary industry within the tourism sector.